The figure of Hades/Plouton in Greek beliefs of the archaic and classical periods - Sekita, K (2015)
The main aim of this work is the presentation, characterisation and review of the image of the Greek underworld deity, Hades/Plouton in Greek beliefs of the Archaic and Classical periods, on the basis of comparison of the preserved literary and epigraphic testimonies with the remains of material culture, and the reconstruction of the most coherent possible image of the god, claimed by scholars to be of little importance to Greek beliefs and to have no cult. The present dissertation liberates the god from long-standing scholarly misconceptions and returns him to his proper place within the Greek pantheon. Its main scholarly contribution and originality can be summarised as follows: (i) Hades is mainly an agricultural deity with a clear cult environment and has more in common with the world of the living than that of the dead; (ii) Hades influenced the representation of other male deities connected with earth: his main attribute, paradoxically the cornucopia or 'horn of plenty', appears for the first time in Greek art in the 6th century BC as exclusively his, and is later ascribed to other deities; (iii) Hades and Plouton were the same deity (Plouton – an Attic instantiation – spread throughout Greece with Attic literature and the Eleusinian cult of Demeter and Kore), sharing the same myths, and both, through the properties inscribed in their names (invisibility in Hades' and corn in Plouton's), referring to the earth; both names are products of the conceptualisation of the world of the dead; (iv) contrary to the prevailing scholarly view, the multiplicity of Hades' names is not exclusively the result of euphemism (which I propose to see rather as a by- product): the nomenclature is more complex and depends principally on cultic or mythological contexts and local tradition. My work not only reconstructs the repertoire of Greek ideas and opinions on Hades and the character of his cult, but also advocates a new understanding of the notion of Greek deity, as metonymy: Hades is representative of a wider class of deities who are concrete and abstract at the same time (like Gaia [the Earth], Uranos [the Sky], Okeanos [the Sea]): they denote a place, a god, a property of something, a form of matter.